2021
DOI: 10.1186/s40001-021-00615-6
|View full text |Cite
|
Sign up to set email alerts
|

Influencing factors of noninvasive positive pressure ventilation in the treatment of respiratory failure: a 10-year study in one single center

Abstract: Background The utilization of noninvasive positive pressure ventilation (NPPV) is becoming more and more common, especially in patients with acute or chronic respiratory failure. The purpose of our study is to analyze the factors that influence the efficacy of NPPV in the treatment of respiratory failure caused by a variety of etiology. Methods From May 2011 to April 2020, patients treated with NPPV during hospitalization in the First Affiliated Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The effects of serum albumin level on NIMV include hypoalbunemia, respiratory muscle weakness, and decreased lung function. 16 In a study evaluating patients with COPD hospitalized in ICU, a negative correlation was found between in-hospital mortality and serum albumin level <3 g/dL. 17 In another study that was conducted in patients with COPD, low serum albumin level was found to be associated with an increase in hospitalization, acute respiratory failure, and mortality.…”
Section: Discussionmentioning
confidence: 98%
“…The effects of serum albumin level on NIMV include hypoalbunemia, respiratory muscle weakness, and decreased lung function. 16 In a study evaluating patients with COPD hospitalized in ICU, a negative correlation was found between in-hospital mortality and serum albumin level <3 g/dL. 17 In another study that was conducted in patients with COPD, low serum albumin level was found to be associated with an increase in hospitalization, acute respiratory failure, and mortality.…”
Section: Discussionmentioning
confidence: 98%
“…34 Wang et al conducted a similar study and reported that serum albumin levels and duration of NPPV treatment were independent risk factors for the efficacy of NPPV treatment in respiratory failure. 35 These results could be combined after a large-scale survey to make a final decision guild for physicians.…”
mentioning
confidence: 99%